Introducing Finite Automata in Basic Education: A Work-in-Progress Proposal - Veiga, Júlia; Cavalheiro, Simone André da Costa; Foss, Luciana (Anais do Workshop-Escola de Informática Teórica (WEIT); 2025: Anais do VIII Workshop-Escola de Informática Teórica, 2025)
This paper presents a proposal for an educational activity to introduce finite automata in Basic Education through a narrative-based approach grounded in Project-Based Learning. Aiming to bridge the gap between Theoretical Computer Science and early school levels, the proposal consists of seven sequential missions where students take on the role of cyber defense agents. Each mission introduces core finite automata concepts – such as states, transitions, acceptance or rejection of a word, and language recognition – using progressive challenges that encourage problem solving and student autonomy.